The link between aphorisms on Jewish eschatological expectation of the anti-Christ and COVID-19 vaccine hesitancy among Pentecostal Christians in Makurdi, Nigeria - Uroko, Favour C.; Okwuosa, Lawrence (Theologia Viatorum (Sorenga), 2022)
This study examines the causal link between vaccine refusal in the Makurdi local government region and aphorisms that deal with the Jewish expectation of the anti-Christ. The Benue State government demanded that schools, companies and religious institutions educate their members about vaccinations. Many residents of Makurdi’s local government communities avoided the coronavirus vaccinations. Even when the state government attempted to restrict certain areas to unvaccinated people, it did not alter the stand of Pentecostal Christians in the state. This study was derived through a phenomenological approach. Findings reveal that aphorisms that concern Jewish expectations of the anti-Christ, such as the mark of the beast, hellfire bound, behaving immorally and animalistic tendencies, amongst others, have sustained vaccine hesitancy in Makurdi. Existing literature has failed to establish a causal link between the Christian understandings of Jewish expectations of the anti-Christ in Makurdi, Benue State. This study attempts to fill this gap. It is believed that the recommendations will speak anew to these challenges.